2020
DOI: 10.1002/mgg3.1474
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in GHR and PLCE1 genes are associated with susceptibility to esophageal cancer

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Dysregulation of GHR signaling is associated with various diseases and chronic diseases, such as acromegaly, cancer, aging, metabolic diseases, fibrosis, inflammation, and autoimmunity ( Strous et al, 2020 ). Wang et al (2020) showed that GHR gene polymorphisms are associated with esophageal cancer in the general population, and GHR signaling can be applied to cancers and other therapeutic strategies ( Gao et al, 2020 ). The extracellular domain of GHR can be cleaved during shedding, reducing the number of cell-surface signaling receptors, which modulate the sensitivity of cells to GH ( Frank, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of GHR signaling is associated with various diseases and chronic diseases, such as acromegaly, cancer, aging, metabolic diseases, fibrosis, inflammation, and autoimmunity ( Strous et al, 2020 ). Wang et al (2020) showed that GHR gene polymorphisms are associated with esophageal cancer in the general population, and GHR signaling can be applied to cancers and other therapeutic strategies ( Gao et al, 2020 ). The extracellular domain of GHR can be cleaved during shedding, reducing the number of cell-surface signaling receptors, which modulate the sensitivity of cells to GH ( Frank, 2001 ).…”
Section: Discussionmentioning
confidence: 99%